(untitled) (Indian Journal of Arid Horticulture, 2025)
Polyploidy has played a pivotal role in the evolution of plants and production of genetic variability. Although, the impact of polyploidy on plant vegetative, floral and fruit characters have been documented indepth, but impact on physiological efficiency has been studied rarely. The present attempt was to screen the polyploid taxa on the basis of physiological parameters in a polyploid sense of ber (Ziziphus mauritiana Lam.). Our results demonstrated that in this species, the polyploidy has shown variable effect in different cultivars. In cv. Illaichi it reduced the physiological efficiency but in cv. Gola it maintained at par.